Bestrophin‐3 is differently expressed in normal and injured mouse glomerular podocytes. (22nd May 2015) - Golubinskaya, V.; Elvin, J.; Ebefors, K.; Gustafsson, H.; Mallard, C.; Nyström, J.; Nilsson, H.
Abstract Aim Bestrophins are putative calcium‐activated chloride channels. Recently, cell‐protective functions for Bestrophin‐3 (Best3) were proposed. Best3 exists in different splice variants. We have here examined expression, alternative splicing and localization of Best3 in mouse podocytes under normal conditions and during endoplasmic reticulum (ER) stress. Methods Best3 expression was determined on the mRNA level using quantitative PCR and on the protein level by immunohistochemistry and Western blotting. Results Staining for Best3 was pronounced in glomeruli and was detected in cultured mouse podocytes. Best3 did not co‐localize with markers for endothelial cells (CD31), podocyte foot processes (synaptopodin) or microtubules (actin). However, immunogold‐based electron microscopy and co‐localization with nestin showed Best3 presence in podocyte primary processes and cell bodies. Only two splice variants of Best3 mRNA (both lacking exons 2 and 3, and one also lacking exon 6), but no full‐length variant, were detected. ER stress induced by lipopolysaccharides in vivo transiently elevated mRNA levels of total Best3 and its two splice variants with different time courses. In cultured podocytes under ER stress induced by thapsigargin, the expression of total Best3, its splice variants and nestin transiently increased with similar time courses. The ER stress marker C/EBP homologous protein (CHOP) and nestin mRNA increased during ER stress in vivo and in vitro. Conclusions Best3 is localized intracellularly in cell bodies and primary processes of mouse podocytes and is co‐localized with nestin. Two splice variants of Best3 are expressed in glomeruli and in cultured podocytes, and their expression is differentially regulated in ER stress.